The Union Government's treatment of the South-West African Mandate (1920-1944) - Pauline Taylor (Department of Historical Studies, 2024)
Very little nas been written on South-nest Africa. l'here are books of travel in the Territory, but my thesis is not concerned with this aspect of the country. some articles on the mandate system as a whole, contain a few pages on the general outlines of the Territory's administration, but these usua11y'treat the subject very broadly. I keenly felt the lack or detailed and 'accurate secondary authorities on the development of the 'territory once it has been a mandate. The only two books of this nature which I found of real value were those of Dr. Wessels "Die .Mnndaat vir Suidwes Afrika .. , and G,L. Steer "Judgment on Ge-rnan ~Jfrioa." Dr. Wessels, however, concentrates more on the constitutional aspect of the ma;ndate, with which only part of my thesis is concerned. I was forced to fall back on primary sources , of which there are many. 1n this respect the annual reports of the ~nion Government on the administration of the mandate, and the .M.inutes of the Permanent Mandates commission, are very valuable as they con ta in much detail. The tteports ,are to be found printed' and bound with the I nnexures to the votes anc P~ceed ings of the House of Assembly; and the Minutes of the Mandates commission are in separate volumes for each session. 'l'he Librarian of the Parliamentary Library kindly allowed me to use the copies of both the .rteports and .Minutes in that library, and also the official Hansard of the debates in Parliament Pnt.l.. the Official Gazettes for south-W'est Africa. I was, ho--ever, handicapped by the fact that, due to the war, the last Heport on South-"'.'est Africa. •...-as that for 1939. Thus for /'~ ' .. the years{l939; to 1944 I had to depend mainly on the Ufficial Gazettes for south-West Africa, and the Official Year ..t,ooks for the I.Inion of Sou th Afr 1 ca. (ii) 1n writing this thesis r have a.ssumed that t.ne reader nas some slight kflowledge of t.he actual working of the mandates system, .its aims and achievements. · . • . o-nly Yurthermore, this thesis is concerned~witb thoee·aspecta of union mandatory rule 1n South-West Africa in whic.h the Permanent uandates Commission showed interett. r am greatly indebted t.o, and take this opportunity of thanking, ·Mr. D .. Yullany of.the Parliamentary Library f-:;r his great helpfulness in tnaking easier my ta.sk of' searching for rn,"il.teria.l; and !.!ias constance Cooper for typing the proofs. 1 have made use of' certain abbreviations, of w.t1ich an expla.natory liot is given below